Knowledge management and firm performance: the mediating effect of entrepreneurial orientation - Franco Ruiz, Camilo (Pontificia Universidad Católica del Perú, 2020)
Entrepreneurship in Latin-American is high compared to other regions. However, there is little innovation. (Lederman, Messina, Pienknagura, & Rigolini, 2014). Lumpkin and Dess (1996) highlighted that holding an Entrepreneurial Orientation (EO) relays on possessing five dimensions that contribute to a Firm Performance (FP). Therefore, a question arises about to what extent firms from emerging markets, such as Colombian companies, possess this orientation and to what extent EO has presented a positive relationship on their FP. In addition, to what extent these firms that implemented Knowledge Management (KM) practices have seen the EO-FP relationship influenced. Few studies are found that reflect the reality of firms from Latin-American markets in this context (Chen, Saarenketo, & Puumalainen, 2016; Martin & Javalgi, 2016) A quantitative, cross-sectional and correlational research was conducted in a sample of Medellin companies. This research found that there is a positive significant relationship between KM and FP on Colombian companies, although this relationship is fully mediated by EO. This should encourage managers from emerging economies to implement KM practices that have a positive effect on their Sales Growth. However, these practices ought be accompanied simultaneously with the promotion of EO. EO must be identified as a “strategic dimension” that companies recurrently present in a given period of time (J. G. Covin & Slevin, 1991). Also, EO does not remain constant over time; companies that possess it may show phases of high EO and low EO, based on their strategic reactions to environmental conditions (Wales, Monsen, & McKelvie, 2011). As KM practices influence positively firm innovation performance (Alegre, Sengupta, & Lapiedra, 2011), companies can expect better innovation performance when they implement KM practices. However, without EO, KM may not have any effect on a company’s Sales Growth, since it needs EO to mediate in such relationship. One of the limitations of this research is that the data collected is mainly from Medellin’s companies. Also, the small sample size of 90 observations may present another limitation. Similar studies from different countries in Latinamerica can be carried out and comparative analyses can be performed with this research in the Colombian context.
Keywords: Empresas--Colombia; Gestión del conocimiento; Investigación cuantitativa; https://purl.org/pe-repo/ocde/ford#5.02.04